THE ANALYSIS OF ELLIPSIS SENTENCE IN “THE GREATEST SHOWMAN” MOVIE SCRIPT - Banjarnahor, Dian Mariana (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2022)
The title of this thesis is The Analysis of Ellipsis Sentence in the Greatest Showman Movie Script. There are two problems of the study in this thesis solved which are, what are the types of ellipsis are found in The Greatest Showman movie script, and how are the syntactical structure of ellipsis found un The Greatest Showman movie script. The data source of this thesis was taken from The Greatest Showman movie script. The theory that used in this thesis proposed by (Halliday & Hassan, 1976) to solve the first problem about types of ellipsis and the second theory proposed by Brown and Miller (1991) to solve the second problem about the syntactic structure. The data in this thesis were collected by using observation method. In order to analyze the data, the writer used qualitative and descriptive methods. The method that applied in presenting the data is formal and informal methods. The result of this study is found one (1) data Nominal Ellipsis, one (1) Verbal Ellipsis and fourteen (14) Clausal Ellipsis.